Relationality in Early Childhood Education in the Context of Climate Crises - Samir Khoja, Zohra (Peer Beyond Graduate Research Conference, 2025)
The kinship relationships and interwoven living in early childhood education context are urgent in an era of climate crises and the Anthropocene. In this article, I delve into the nested relationships between humans with more-than-human forms. My purpose is to create ethical spaces of dialogue that weave together stories-beginning with my own childhood stories, extending to the narratives of South Asian early childhood educators in Alberta and tying knots with Indigenous stories.